UTILIZING FLANEL FABRIC TO BE A TAKSI (TAS KEREASI SENDIRI) BAG OF YOUR OWN CEATIONS - Zulfahita Zulfahita; Hilda Januarti; Giri Wulandari; Elsi Tamara; Orlando Orlando (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2019)
For the student creativity program in this entrepreneurship class, we run a business program for making our own bags from flannel. The flannel cloth itself is easy to find in the nearest shops and the price is also quite affordable. Besides being easy to get, flannel is also easy to make several forms of crafts, one of which is a bag. The bag that we are going to make is a sling bag model, where this model is loved by children today or it can be called a trend. Here what we need in addition to tools and materials is that we need skills and creative power. So that the bag that we will make can attract consumers to buy. In the community, there are many bags that make consumers want to buy them, but the prices are less affordable for consumers. Therefore, we take advantage of this situation to make bags of our own creations in order to help consumers to support their appearance with the bags that we make, of course, these bags are cheap in the pockets of students and teenagers.